THE INFLUENCE OF LIVE STREAMING, CASHBACK, AND FREE SHIPPING ON PURCHASING DECISIONS PURCHASE OF TIKTOK SHOP (A STUDY OF MANAGEMENT STUDENTS AT MALIKUSSALEH UNIVERSITY) - Nidea Rinzeni; Adnan; Widyana Verawati Siregar; Rusydi Abubakar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study aims to examine the influence of live streaming, cashback, and free shipping on purchasing decisions on TikTok Shop (a study of management students at Malikussaleh University). Data in this study was collected using a questionnaire as a data collection instrument. The sample size for this study was 102 respondents. This study employed a quantitative approach using multiple linear regression analysis and was processed using the SPSS (Statistical Package for the Social Sciences) software. Hypotheses were determined using SPSS version 25.0. The results of this study indicate that, partially, the Live Streaming variable has a positive and significant effect on purchasing decisions on TikTok Shop, statistically 0.001 < 0.005, and has a t-value > t-table, 2.907 > 1.660. The Cashback variable has a positive and significant effect on purchasing decisions on TikTok Shop, statistically 0.004 < 0.005, with a t-value > t-table, 2.771 > 1.660. Furthermore, the Free Shipping variable has a positive and significant effect on purchasing decisions on TikTok Shop, statistically 0.000 < 0.005, with a t-value > t-table, 9.825 > 1.660. The adjusted R-square value for the independent variables—live streaming, cashback, and free shipping—indicates that 70.1% of the variance is explained by these variables, while the remaining 29.1% is explained by other variables not included in this study.